DEVELOPMENT OF TRADITIONAL FISH PRESERVATION TECHNIQUES ON THE COASTAL COAST OF BENGKULU CITY E-BOOKLET LEARNING MEDIA USING ADDITIVES - Pratiwi, Fira; Uliyandari, Mellyta; Yani, Ariefa Primair; Koto, Irwan; Karyadi, Bhakti (JURNAL SPEKTRA, 2024)
This research aims to develop e-booklet learning media for traditional fish preservation techniques on the coast Bengkulu City. This research uses the Borg & Gall model which is carried out to the fourth stage, namely 1) research and data collection (research and information ), (2) planning (planning), (3) developing a product draft (developing a preliminary form of a product), (4) field trials (preliminary field testing). The research instruments included observation sheets, teacher interview sheets, student readability test questionnaires and expert validation sheets. The research results show that the e-booklet on traditional fish preservation techniques on the coast of Bengkulu City as a learning medium for an additive material for students is very suitable for use based on the results of validation tests. Students' responses to the readability of the e-booklet on traditional fish preservation techniques on the coast of Bengkulu City as a learning medium for additive material for students showed the very good category. In conclusion, the e-booklet on traditional fish preservation techniques on the coast of Bengkulu City as a learning medium for additive material is very suitable for use in learning science and additive material for class VIII SMP.